PERAWATAN LUKA DIABETES PADA DAERAH SUB SCAPULARIS DI UNIT PERAWATAN HOME CARE - Sukmawati, Sukmawati; Laitung, Baharia; Yusuf, Saldy (in process)
Background As one of top ten Diabetes Mellitus (DM) country, prevalence of diabetic foot ulcers (DFU) in Indonesia is high. However there is increasing number of diabetic ulcer non foot (DUNF) in clinical setting. Thus, the aim of this study is to describe the wound care process, healing process, and cost analysis of DUNF. Method A case report study based on retrospective data including; demography data, history of DM and history of DFU recorded by minimum data sheet (MDS). Ulcer pictures were taken by digital camera healing process evaluated by using Barbara Bates Jensen (BBJ) score. Results Patient 44 years, female, have been diagnosed as diabetic since 2013. DUNF located at sub scapularis sinistra with duration of treatment was 95 days and frequency of dressing changes was 15 times. Initial BBJ score was 27 and decreased to be 13 at the end of treatment (healing rate by BBJ score: 0.14/day). Cost of dressing (range Rp. 25.000 â Rp. 160.000) with mean cost Rp. 100.437. Proportion of cost was 53.3 % for dressing. Correlation between severity of ulcer and cost (R2 = 0.570 p = 0.024). Conclusion The occurrence and recurrence of diabetic ulcer can be any part of body including sub scapular region. Current study confirmed that wound care process takes three months until epitealization with mean cost relative expensive.